Targeting GluN2B/NO Pathway Ameliorates Social Isolation-Induced Exacerbated Attack Behavior in Mice - Weiqing Fang; Xiaorong Wang; Miao Cai; Xinxin Liu; Xuemeng Wang; Wen Lu; Wen Lu (Frontiers Media S.A., 2021)
Exacerbated attack behavior has a profound socioeconomic impact and devastating social consequences; however, there is no satisfactory clinical management available for an escalated attack behavior. Social isolation (SI) is widespread during this pandemic and may exert detrimental effects on mental health, such as causing heightened attack behavior. To explore the therapeutic approaches that alleviate the SI-induced heightened attack behavior, we utilized pharmacological methods targeting the GluN2B/NO signaling pathway during the attack behavior. Ifenprodil and TAT-9C peptide targeting GluN2B showed that the inhibition of GluN2B mitigated the SI-induced escalated attack behavior and the SI-induced aberrant nitric oxide (NO) level in the brain. Additionally, the potentiation of the NO level by L-arginine reversed the effects of the inhibition of GluN2B. Moreover, we showed that high doses of L-NAME and 7-NI and subeffective doses of L-NAME in combination with ifenprodil or TAT-9C or subeffective doses of 7-NI plus ifenprodil or TAT-9C all decreased the SI-induced escalated attack behavior and reduced the NO level, further supporting the idea that GluN2B/NO signaling is a crucial modulator of the escalated attack behavior.